PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE GUIDED NOTE TAKING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 X KOTO SINGKARAK - Sari, Dahlia Purnama; Zuzano, Fazri; Febriana, Rina (STKIP PGRI Sumbar, 2013)
This reseach has background by understanding of concept so that student canât contrutioning to their own concept understanding and more of the student canât aplicate the concept problem solving which is they want. This research has purpose for to know the impact of active learning strategy type Guided Note Taking to student mathematic concept understanding on the subject aljabar factor. Kind of this research is experiment with plan random on subyek. The population is VIII SMPN 1 X Koto Singkarak and sample it VIIIC as experiment class and VIIIB as control class. This research use instrument is essay, that test about understanding of mathematical concepts student consist of 9 itemÂ with reliability testÂ 0,865. By virtue of data analysis get average of result learning of student experiment class better than control class. Hypothesis use test t-one way. Result thitung = 2,7248 andÂ ttabel = 1,6795, because thitung > ttabel so hypothesis acceptable. So the conclusion is learning with active learning type Guided Note Taking better than conventional learning at VIII SMPN 1 X Koto Singkarak